2014
DOI: 10.1016/j.jvlc.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

User-driven visual composition of service-based interactive spaces

Abstract: ObjectiveThe idea is to replace fixed, pre-packaged applications with flexible composition environments that, thanks to a separation among data, functions and presentations, make interactive environments "emerge" at run-time based on composition actions performed by end users. MethodsThis paper describes an approach for the lightweight construction of integrated, situational work-spaces pervasively accessible and sharable through a variety of devices. Specific emphasis is posed on the adoption of a composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 40 publications
(40 reference statements)
0
37
0
Order By: Relevance
“…Some field studies that we conducted in the past to validate our prototypes [4,5] revealed that mashups generally lack data manipulation functions that end users would like to exploit in order to "act" on the extracted contents, e.g., functions that allow to perform tasks such as collecting&saving favourites, comparing items, plotting data items on a map, inspecting full content details, organizing items in a mind map in order to highlight relationships. In this section, we remark another very innovative feature of EFESTO: it offers tools that enable specific tasks, allowing users to manipulate the information in a novel fashion, i.e., without being constrained to pre-defined operation flows typical of pre-packaged applications.…”
Section: Actionable Ui Componentmentioning
confidence: 99%
See 3 more Smart Citations
“…Some field studies that we conducted in the past to validate our prototypes [4,5] revealed that mashups generally lack data manipulation functions that end users would like to exploit in order to "act" on the extracted contents, e.g., functions that allow to perform tasks such as collecting&saving favourites, comparing items, plotting data items on a map, inspecting full content details, organizing items in a mind map in order to highlight relationships. In this section, we remark another very innovative feature of EFESTO: it offers tools that enable specific tasks, allowing users to manipulate the information in a novel fashion, i.e., without being constrained to pre-defined operation flows typical of pre-packaged applications.…”
Section: Actionable Ui Componentmentioning
confidence: 99%
“…The model clarifies the main ingredients that are needed to design a platform that enables non-technical end-users to create component-based interactive workspaces by aggregating and manipulating data available on distributed online resources. The main goal is to highlight the features that can lead to frameworks able to reduce the end-users' effort for the development of interactive workspaces [5], by maximizing the reuse of UI components.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our approach is characterized by the adoption of design environments that, in line with recent approaches to visual programming of mashups, make intensive use of high-level visual abstractions [15,4]. Visual paradigms indeed hide the complexity typical of service composition, data integration and the programming of context-aware mobile apps, and assist CAMUS designers (even if non-experts in these technologies) in the creation of multi-device personalized applications.…”
Section: The Camus Methodologymentioning
confidence: 99%